Jack - Miles, Ellen (Miles, Ellen. Puppy place., 2009)
"Aunt Amanda knows that Lizzie can't turn down the chance to foster a new puppy, so she brings over a boxer - who loves to chew up everything in sight! Can Lizzie find the right owner for this special pup before her house is destroyed?"--